Implementation of Artificial Intelligence by Kominfo in the enforcement of pornographic content on social media Twitter (X) - Fahririn; Cakra Heru Santosa; M. Ihsan Maulana (Walisongo Law Review (Walrev), 2024)
This research is motivated by the increasing prevalence of pornographic content, which has significant psychological, social, and economic impacts on Indonesian society. The study examines the application of Artificial Intelligence (AI) by the Ministry of Communication and Informatics (Kementerian Komunikasi dan Informatika, Kominfo) in enforcing laws against pornographic content on Twitter (now known as X). Employing a descriptive qualitative method with a case study approach, the research involved in-depth interviews with 15 key informants. The findings reveal that Kominfo’s AI system utilizes a layered detection model integrating computer vision and natural language processing, achieving an accuracy rate of approximately 85% for visual content and 75% for textual content. The system automates around 80–85% of the detection process through deep packet crawling and inspection techniques. Despite these advancements, law enforcement efforts face several challenges, including a high rate of false positives, difficulties in cross-platform coordination, and limited contextual understanding of local cultural nuances. The study concludes that effective enforcement requires developing more adaptive algorithms supported by comprehensive, Indonesia-specific datasets; enhancing coordination with global social media platforms; establishing an integrated task force; and creating a transparency and accountability framework to ensure a safer digital ecosystem. Penelitian ini dilatarbelakangi oleh meningkatnya prevalensi konten pornografi yang berdampak signifikan terhadap aspek psikologis, sosial, dan ekonomi masyarakat Indonesia. Studi ini menelaah penerapan Kecerdasan Buatan (Artificial Intelligence, AI) oleh Kementerian Komunikasi dan Informatika (Kominfo) dalam penegakan hukum terhadap konten pornografi di platform media sosial Twitter (kini dikenal sebagai X). Dengan menggunakan metode kualitatif deskriptif melalui pendekatan studi kasus, penelitian ini melibatkan wawancara mendalam dengan 15 informan kunci. Hasil penelitian menunjukkan bahwa sistem AI Kominfo menerapkan model deteksi berlapis yang mengintegrasikan computer vision dan natural language processing, dengan tingkat akurasi sekitar 85% untuk konten visual dan 75% untuk konten tekstual. Sistem ini mampu mengotomatisasi sekitar 80–85% proses deteksi melalui teknik deep packet crawling dan inspection. Meskipun demikian, pelaksanaan penegakan hukum masih menghadapi sejumlah tantangan, antara lain tingginya tingkat false positives, kesulitan koordinasi lintas platform, serta keterbatasan pemahaman terhadap konteks budaya lokal. Penelitian ini menyimpulkan bahwa efektivitas penegakan hukum memerlukan pengembangan algoritma yang lebih adaptif dengan dukungan data set komprehensif yang sesuai dengan konteks Indonesia, peningkatan koordinasi dengan platform media sosial global, pembentukan satuan tugas terpadu, serta pengembangan kerangka transparansi dan akuntabilitas guna menciptakan ekosistem digital yang aman dan berintegritas.Keywords: Artificial Intelligence; Pornographic Content; Law Enforcement; Twitter (X)